IMPLEMENTASI MODEL PEMBELAJARAN ADVANCE ORGANIZER PADA MATA PELAJARAN IPA SEKOLAH MENENGAH - ' Abna Hidayati, Syafril, Fakhrul Azhar (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
The implementation of conventional learning, especially in science subjects in secondary schools, has many obstacles, as a result, learning motivation and student interest are low. In connection with this, an innovative learning model is needed, one of which is the Advance Organizer learning model with multimedia assistance. This research uses a quantitative method in the form of Quasy Experiment. This type of research is quantitative, with a population of all VIII grade students at State Junior High Schools in Padang City. The sample was taken using a purposive technique, namely SMP N 34 Padang. class VIII1 as the experiment and class VIII2 as the control class, each of which numbered 20 people. This type of research data is in the form of data on student learning outcomes and the source of the data is student scores. The data obtained were analyzed using the t-test. The results showed that the average value of the experimental class using the multimedia-assisted Advance Organizer model was quite significant with t count greater than the table. This means that the application of the Advance Organizer model assisted by Prezi media has an effect on student learning outcomes.Keywords : Advance Organizer, Multimedia, Science Learning, Secondary School